Decrease the Level of Complaints in a Company of Air Compressors through Lean Manufacturing Based On Dmaic Methodology - Eyzaguirre Monasterio, Lucía Fabiana (2024)
In the field of mining and construction, the machinery and equipment subsector face challenges in customer service quality due to repeated reprocessing caused by a lack of preventive maintenance. This research proposed a solution based on Lean Manufacturing by applying Total Productive Maintenance (TPM), following the steps of a DMAIC methodology, and conducting simulations using Arena software. The initiative focused on streamlining the rental process, reducing response times, and improving the reliability of compressors. Positive outcomes were anticipated, including increased equipment availability, reduced response times, a decrease in the failure rate, and improved customer satisfaction. Furthermore, simulation results revealed a significant transformation: the average customer service time decreased by 35.49% (from 1714.70 to 1106.03 minutes), and the average preparation time of a compressor before rental decreased by 32.81% (from 2750.53 minutes to 1847.86 minutes). In the economic analysis, the feasibility of the proposal was demonstrated using @risk software, with a Net Present Value (NPV) of $139,024 and an Internal Rate of Return (IRR) of 34.83%, surpassing the Cost of Capital (COK). This research aimed not only to enhance key performance indicators but also to position the company as a leader in efficiency and customer satisfaction in the competitive machinery and equipment sector. This holistic approach not only strengthened operational efficiency and cost reduction but also contributed to the sustainable development of the machinery and equipment sector. © 2024, Avestia Publishing. All rights reserved.